Coronary intervention versus myocardial revascularization surgery in patients with multivessel disease. - Dra. Mirtha López Ramírez (ECIMED, 2017)
Ischemic heart disease is among the leading causes of death in Cuba and worldwide; Coronary interventionism (PCI) and coronary surgery (CABG) are pillars of the treatment of myocardial revascularization. Objective: To determine the results of multivessel PCI in patients with multivessel coronary artery disease. Method: prospective cohort study in the Cardiocentro of the "Hermanos Ameijeiras" hospital, between January 2011 and January 2013 for revascularized patients under PCI and from March 2012 to March 2014 for revascularized patients by surgery. The sample consisted of 87 patients from the PCI group and 91 patients with CABG. The results were presented in percentages, Kaplan-Meier method was used to estimate survival. Results: revascularized patients with PCI 3.4% died due to heart failure, 2.3% had non-fatal infarction, and 10.3% required new revascularization. Event-free survival per year was 89.2%. Patients revascularized by surgery had a 6.6% cardiac cause mortality, 16.5% presented non-fatal MI, and 5.5% required revascularization. In the RCM, overall survival at 93.3%, the probability of dying from cardiac causes was 6.7%, and event-free survival (IMA / RV / Death) was 88.7% And the probability of having events was 11.3%. Conclusions: Myocardial revascularization surgery showed similar results regarding event-free survival with respect to coronary interventionism, the probability of death was very low and the frequency of revascularization was lower.